Experimental method to analyze the oil mist impingement over an insert used in MQL milling process. (May 2016) - Duchosal, Arnaud; Werda, Sana; Serra, Roger; Courbon, Cédric; Leroy, René
Highlights: Oil mist imprint is measured with blotting paper and 3D-profilometer. Both methods are independent and tend to the same imprint results. Only the flute shape has an influence on the oil mist behavior. Good lubrication is ensured in low rotation velocity (5000 rpm). Best lubrication conditions are obtained with 75° oriented canalizations. Abstract: This paper proposes an original method to determine the oil mist impingement over an insert based on different machining configurations (rotation velocities) and different inner canalization designs, without material removal, on milling tool. The oil mist spray is determined using different holders as an insert. Glass plate and blotting paper are used and evaluated in this work to get as much information as possible, based on micro–macro scale observations. The imprint size of the oil mist spray distribution, the particle sizes and the fluid film formation have been studied to determine the effects of the different configurations on the oil mist impingement behavior. The droplet impingements and distributions on the glass plate are analyzed under a 3-D profilometer (microscopic scale). On the blotting paper, the distributions are analyzed with pictures of the oil marks (macroscopic scale). This original method gives quite fast particle distributions that can be used in industry. The different experimental results give large information about the oil mist behavior sprayed on the glass plate. Increasing rotation velocities increases the oil mist amount in the cutting area. Increasing the canalization orientation design gives a better focused spray. The rake angle has strictly no influence on the oil mist spray distribution. But sputtering effects have been highlighted and should be avoided to keep MQL efficiency.